2018
DOI: 10.14738/abr.611.5590
|View full text |Cite
|
Sign up to set email alerts
|

A structural model of total quality management, kaizen, operational performance on service quality and patient satisfaction

Abstract: A structural model of total quality management, kaizen, operational performance on service quality and patient satisfaction. ABSTRACTTests are the strength effect of total quality management (TQM), Kaizen and operational performance on service quality and patient satisfaction. The other part we will test is the service quality as a mediation role to explain the effect of total quality management (TQM), Kaizen and operational performance on patient satisfaction. This research was conducted in the city of Makass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Next, we provide banking sector literature on the impact of total quality management on innovation performance, intervened by innovative behaviour. We also offer banking sector literature on the conditional roles of external factors on the total quality managementinnovative behaviour nexus, since available literature precludes information on the banking sector, concentrating on others sectors like education (Kingi and Mwangangi, 2017;Koomson, 2022;Sweis et al, 2020), healthcare (Abadi et al, 2018;Abdallah and Mohamed, 2018;Alomari et al, 2020;Baidoun et al, 2018;Khalil and Muneenam, 2021;Mosadeghrad and Afshari, 2020;Zaid et al, 2020), agro-based (Akanmu et al, 2020), automotive (Petcharit et al, 2020), air conditioning (Mitreva et al, 2020), manufacturing (Lizarelli et al, 2023;Phan et al, 2019;Sila, 2018;Udofia et al, 2021), shipping (Thai and Jie, 2018), research & development (Gupta et al, 2017) and hospitality (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we provide banking sector literature on the impact of total quality management on innovation performance, intervened by innovative behaviour. We also offer banking sector literature on the conditional roles of external factors on the total quality managementinnovative behaviour nexus, since available literature precludes information on the banking sector, concentrating on others sectors like education (Kingi and Mwangangi, 2017;Koomson, 2022;Sweis et al, 2020), healthcare (Abadi et al, 2018;Abdallah and Mohamed, 2018;Alomari et al, 2020;Baidoun et al, 2018;Khalil and Muneenam, 2021;Mosadeghrad and Afshari, 2020;Zaid et al, 2020), agro-based (Akanmu et al, 2020), automotive (Petcharit et al, 2020), air conditioning (Mitreva et al, 2020), manufacturing (Lizarelli et al, 2023;Phan et al, 2019;Sila, 2018;Udofia et al, 2021), shipping (Thai and Jie, 2018), research & development (Gupta et al, 2017) and hospitality (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Abdallah and Mohamed (2018) indicated a substantial favourable connection between total quality management mindfulness and satisfaction of patients using data from caregivers in Egypt. Abadi et al (2018) also discovered that total quality management favourably contributed to the satisfaction of 398 patients in Indonesia. Thai and Jie (2018) suggested that total quality management encouraged organisational performance of container shipping companies in Singapore.…”
Section: Theoretical Development Resource-based Theory Of a Firmmentioning
confidence: 98%
See 3 more Smart Citations